Frequencies of pure olive oil at temperature between 50°C to 25°c - Abdul Hamid, Syamsul Bahrin; Azman, Noor Ajeera (Pen2Print, 2021)
A study was carried out to determine the effect of temperature between 50°C to 25°C on the frequency of pure olive oil bought from Malaysia local market. An evaluation module, TDC1000-TDC7200EVM was connected to an ultrasonic 1MHz transducer to transmit and receive the ultrasound wave. The ultrasound wave signals were measured in time of flight values, where the time was calculated when the ultrasonic first tigger the ultrasound wave and when the ultrasonic receive the returning echo of the ultrasound wave. The time of flight data were converted to frequency and monitored the effect at different temperature. Based on the results, at the lowest temperature, the pure olive oil have the highest frequency peak, and vice versa. electronic document is a “live” template and already defines the components of your paper